Analisis Tingkat Pengembalian Saham pada Industri Dasar Kimia Subsektor Logam - Gelar Rialdi Pratama; Erry Sunarya; Acep Samsudin (BUDGETING : Journal of Business, Management and Accounting, 2020)
This study aims to determine how much return on shares contained in PT. Lion Metal Work with the Earning Per Share (EPS) method, and also wants to know the rate of return on debt at PT. Lion Metal Work with the Debt To Equity Ratio method. The results of this study state that the value of Earning Per Share in 2015-2016 has increased above the industry average standard, and in 2017 the company has decreased below the industry average standard, while the results of the Debt to Equity Ratio state that the company in 2015-2017 has increased but the value of the Debt To Equity Ratio is less than the industry average standard. The company's problems are in the performance of companies that are experiencing a decline and the value of profits continues to decline and the total debt continues to grow. Conclusions, based on the results and analysis of research data, the return of company shares is not good, as well as the return of debts that are categorized as small or not good because of an increase in debt from year to year while the rate of return on corporate debt is small. Keywords: Earning Per Share, stock returns, Debt To Equity Ratio.